2005
DOI: 10.1007/s10549-005-9007-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the sentinel and non-sentinel lymph node metastases in breast cancer

Abstract: The sentinel lymph node (SLN) is the only focus of axillary metastasis in a significant proportion of patients. In this single institutional study, clinicopathologic characteristics were investigated to determine the factors predicting the status of a SLN biopsy and the metastatic involvement of non-SLNs. Data were retrospectively reveiwed for 400 consecutive patients with clinical T1/T2 N0 breast cancer who underwent a SLN biopsy including axillary and/or internal mammary lymph nodes. The SLNs were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 52 publications
(92 reference statements)
3
44
0
1
Order By: Relevance
“…Similarly, according to a study by Baxter et al (2004), the rate of mastectomy decreased from 43% in 1992 to 28% in 1999, and the rate of ALND decreased from 34 to 15% during the same time period (Baxter et al, 2004). In agreement with all these studies, we also found an increased rate of BCS and SLNB in patients with DCIS or DCISM at our institution after 2004, whereas the mastectomy rate and ALND rate were significantly decreased between 2004 and 2008 compared to the corresponding rates for the period between 1996-2004 (Ozmen et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, according to a study by Baxter et al (2004), the rate of mastectomy decreased from 43% in 1992 to 28% in 1999, and the rate of ALND decreased from 34 to 15% during the same time period (Baxter et al, 2004). In agreement with all these studies, we also found an increased rate of BCS and SLNB in patients with DCIS or DCISM at our institution after 2004, whereas the mastectomy rate and ALND rate were significantly decreased between 2004 and 2008 compared to the corresponding rates for the period between 1996-2004 (Ozmen et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The median number of nonsentinel axillary LNs resected was 13 (3 -29). Metastatic involvement of at least one nonsentinel axillary LN was found in 37 of 65 (56.9%) patients, with the median number of involved nonsentinel axillary LNs being 3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Neither the size of the primary tumor, nor Nottingham grade, nor estrogen receptor, progesterone receptor, or Her2 status, nor the involvement of more than one sentinel LN, were correlated with the presence of nonsentinel LN metastases.…”
Section: Resultsmentioning
confidence: 94%
“…ECI of the axillary lymph node is an index for aggressive tumor behavior in breast cancer and the patients with ECI have an obvious poorer outcome (Altinyollar et al, 2007). In many studies, ECI was a predictor of NSLNM (Stitzenberg et al, 2003;Van Zee et al, 2003;Ozmen et al, 2006;Beriwal et al, 2008;Fujii et al, 2010;Boler et al, 2012;Derici et al, 2012;Scomersi et al, 2012), although in some other studies this relationship was not found or evaluated (Yu et al, 2005;Wada et al, 2006;Guray Durak et al, 2011). In a meta-analysis by Degmin et al, the size of the SLN metastasis, ECI, primary tumor size, and LVI, were defined as predicting factors of NSLNM (Degnim et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have revealed that multifocality of the primary tumor is a predictor of NSLNM (Ozmen et al, 2006;Fougo et al, 2009). In the present study, the relationship between multifocality of the primary tumor and NSLNM was significant in univariate analysis, but it was not significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation